Determinant of Property Price Through The Monetary Variables: An ARDL Approach - Mahrus Lutfi Adi Kurniawan; Uswatun Khasanah; Siti 'Aisyah Baharudin (Muhammadiyah University Press, 2023)
The 2008 financial crisis demonstrates that studies on property price volatility are important because it impacts domestic economic conditions. This study identifies the volatility of property prices through monetary variables. This current study employs the ARDL method to determine the effect of monetary variables in the short and long term. The study results show that GDP as a proxy for income negatively affects residential property prices in Indonesia, and inflation positively affects property prices. There is a difference in the effect of domestic interest rates on property prices where there is a direct effect on domestic interest rates followed by the COVID-19 crisis. Meanwhile, foreign interest rates have a negative effect in the short term and a positive effect in the long term. This study implies that strong monetary operation through interest rates can maintain public expectations of prices, especially property prices.